Atlas of Surgical Correction of Female Genital Malformation - Zhu, Lan; Wong, Felix; Lang, Jinghe (Springer Netherlands : Imprint: Springer, 2015)
This book discusses a rare form of female genital tract abnormality. It starts with an introduction to modern pre-surgical diagnostic tools, including hysterosalpingography, 3D ultrasound and MRI. From external to internal genitalia, this book introduces all commonly known malformations, as well as a variety of rare congenital malformations of the female genital tract. For each malformation, it includes indications, timing, surgical illustration, contraindication, anaesthesia, surgical procedure, postoperative treatment, and key points. In order to facilitate understanding, extensive illustrations and surgical images are also provided. This text offers a comprehensive guide for clinicians, helping them to accurately diagnose and treat these patients, who may present with different clinical manifestations. The authors are well-known gynecologists actively involved in the diagnosis and treatment of difficult diseases. Editors Lan Zhu and Jinghe Lang are Professors at the Department of Obstetrics and Gynecology, Peking Union Medical College Hospital, Beijing, China. Editor Felix Wong is a Professor at the Department of Obstetrics and Gynaecology, Liverpool Hospital, Liverpool, Australia. Professor Lang is also an Academician of Chinese Academy of Engineering.